Manifestations of Place in the Poetry of Fahad Al-Askar - Binarabi, Khalifa Yaseen (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to shed light on the experience of the Kuwaiti poet Fahad Alaskar and its connection with the place considered a fundamental element in the formation of the poetry experience, looking at the particular social conditions that he has experienced. So, the poet tends to refer to the place in many of his poems to indicate a wide variety of functions in his poetic experience. Methods: This study adopts the descriptive-analytic approach, where it seeks to thoroughly dismantle the subjective state of the poet Fahd Alaskar under the harsh social conditions he has experienced, and to thoroughly study the parts of his connection with the place, by analyzing the elements of the places in his poems, dismantling their ramifications, and then interpreting their different psychological dimensions in attempt to generally arrive at a specific assessment of his poetic experience. Results: The place is of great importance to Fahad Al-Askar, as his suffering is considered primarily social, and there are numerous significant places in his poetry, including the seashore, the homeland, and the Great Homeland. Women also have a remarkable presence in his poetry. The place also does multiple functions in his poetry, on top of which is the psychological function, as it constitutes a fertile memory for the poet, as he used to evoke places to recreate past memories, which are generally characterized by being blissful. Nationalism, for Al-Askar, has a role in highlighting the places associated with the major Arab issues, specifically the Palestinian cause. Women also constitute a great part of his experience; thus, he uses the place to express his repeated disappointments in that regard with absolute sincerity. Finally, from the poet’s perspective, the place itself was not responsible for his suffering. The responsibility lies primarily with the cruel people who were there in those places. Conclusions: The place, for Fahd Al-Askar, was not just static, but it had multiple extensions and functions, through which he was able to open up to many social, psychological and political prospects.